LOCAL PERCEPTIONS TOWARDS THE ENVIRONMENTAL IMPACT OF TOURISM ON THE CHÀM ISLANDS, VIETNAM - Ngoc Chau Ngan, Nguyen; Omar, Shida Irwana; Nhu Ngoc, Ho (PLANNING MALAYSIA, 2022)
Local perceptions have the most significant impact on the sustainable tourism practices in a region. This study used the Social Exchange Theory (SET) to examine how local perceptions towards the environmental costs and benefits affect their support for tourism development. The study involved 300 residents of the Chàm Islands. Two factors that affect local perceptions towards the environmental costs and benefits; namely, community concern and eco-centric attitudes; were assessed. Two factors were found to have a positive effect on the perceived environmental costs while community concern had influence on perceived environmental benefits. Local perceptions towards the environmental costs and benefits also had a positive and significant correlation with their support for tourism development. Therefore, the locals still support tourism development even though they believe the environmental costs outweigh its benefits. The government and tourism planners may use the findings to guide local perceptions towards the environmental impacts to develop sustainable practices.